Феноменологія буттєвого досвіду - Солонько, Леонід; Solonko, Leonid (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено, як свідоме звернення до буттєвого досвіду може стати ефективним засобом розв’язання екзистенційних проблем, які стоять перед сучасною людиною. Обґрунтовується думка про те, що легітимізація й уписання буттєвого досвіду в сучасний культурний контекст неможливі без його адекватної раціональної інтерпре¬тації. Відзначено, що опис феноменології буттєвого досвіду – важлива передумова наукового розу¬міння цього явища. The article shows that conscious appeal to the experience of beingness can be an effective instrument of resolving the existential problems facing modern man. The author substantiates the idea that the legitimisation and inscribing existential experience in the contemporary cultural context is impossible without its rational interpretation. It is shown that the description of the phenomenology of existential experience is an important step in the scientific understanding of this phenomenon. Attention is drawn to the fact that for all the doctrinal differences between the various religious systems, their basic phenomenology of religious experience is practically identical. To illustrate this situation, in the article it was attempted appeal to the classical religious texts belonging to the different, often quite distant, cultural traditions, such as Buddhism and Christianity. Hence the conclusion there is one, the same for all, universal experience lays in the basis of any religious system – the experience of beingness, deployment of which leads to the release of the existential problems that the person is experienced as attainment of salvation, grace etc.
Existential Experience Phenomenology
Keywords: буттєвій досвід; cпасіння; благодать; транс; архетип; психотехніка; existential experience; salvation; grace; trans; archetype; psychotechnique